Visual methods in social research - Banks, Marcus; Zeitlyn, David (SAGE, 2015)
"Combining the theoretical, practical and technical the authors discuss changing technologies, the role of the internet and the impact of social media. Presenting an interdisciplinary guide to visual methods they explore both the creation and interpretation of visual images and their use within different methodological approaches."--Back cover.